Analgesic Activity of Methanolic Extract of Tubers of Arisaema tortuosum (Wall.) Schott. in Swiss Albino Mice - Chakraborty, Priyanka; Bala, Nripendra Nath; Das, Sudipta (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The aim of the the present study was to investigate the analgesic activity of methanolic extract of Arisaema tortuosum (MEAT) using acetic acid-induced writhing and hot plate methods. The hot plate method is useful in elucidating centrally mediated antinociceptive responses, while acetic acid-induced writhing is the chemically induced pain of peripheral origin. The MEAT was used at doses of 50, 100, 200 and 400 mg/kg body weight on swiss albino mice. The percentage inhibition of the abdominal constriction reflex increased dose dependently in case of acetic acid-induced pain and in the hot plate method model the extract at the dose of 400 mg/kg significantly increased the pain reaction time (PRT). These studies conclude that A. tortuosum (Wall.) Schott. tuber possesses analgesic activity in a dose dependent manner. In case of acetic acid-induced pain, the extract at the dose of 400 mg/kg body wt. showed 41.19% inhibition of writhing reflex. In case of hot plate method, after 60 minutes the PRT increased to 7.47 ± 0.05 seconds for the extract at the dose of 400 mg/kg body wt. Dhaka Univ. J. Pharm. Sci. 17(1): 37-41, 2018 (June)